Impacts of global change on the Nile basin: Options for hydropolitical reform in Egypt and Ethiopia - Martens, Anja Kristina (International Food Policy Research Institute, 2011)
This paper analyzes drivers of global change and their impacts on the current and future availability and accessibility of water resources in the Nile Basin. Drivers include changes in demography, climate, the socioeconomy, and politics, all of which are likely to increase the demand for freshwater and thus competition over its use across riparian countries. As a result of historic bilateral agreements, Egypt, as the most downstream country, uses the lion's share of the Nile's waters, which makes reallocation particularly difficult. Egypt is nearly totally dependent on water from upstream countries but considers any change of the status quo a threat to its national (water) security. Ninety-six percent of Egypt's water originates outside its territory—86 percent in Ethiopia. This paper assesses the special upstream-downstream relationship in the Nile Basin and the potential for change as a result of global change. It hypothesizes that under global change, not only will water availability in the Nile Basin change but so will the current hydropolitical situation in the basin. In any case, meeting the challenges in the Nile Basin depends on cooperation among countries and regulation of competing interests and demands. Avenues for hydropolitical reform, including the Nile Basin Initiative, and the role of China and other donors or investors are discussed. The findings—that global change might well bring down the old hydropolitical regime—are confirmed by recent developments, in particular, the signing by five upstream countries of a new framework agreement for management and development of the Nile Basin.